2022
DOI: 10.3390/plants11151993
|View full text |Cite
|
Sign up to set email alerts
|

Calluna vulgaris as a Valuable Source of Bioactive Compounds: Exploring Its Phytochemical Profile, Biological Activities and Apitherapeutic Potential

Abstract: Calluna vulgaris, belonging to the Ericaceae family, is an invasive plant that has widely spread from Europe all across Asia, North America, Australia and New Zealand. Being able to survive in rigid soil and environmental conditions, it is nowadays considered to be of high nature-conservation value. Known for its nutritional and medicinal properties, C. vulgaris stands out for its varied physiochemical composition, spotlighting a wide range of biological activity. Among the most important bioactive compounds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 231 publications
0
1
0
Order By: Relevance
“…Honey type is a crucial factor determining the levels of phenolic and flavonoid compounds and, thus, different antibacterial behaviors. In dark forest honey and honeydew honey, these compounds performed successfully against Gram-positive and Gram-negative bacteria [136][137][138][139][140][141].…”
Section: Php?ids[]=saandids[]=egandids[]=ptandids[]=b Randids[]=it (A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Honey type is a crucial factor determining the levels of phenolic and flavonoid compounds and, thus, different antibacterial behaviors. In dark forest honey and honeydew honey, these compounds performed successfully against Gram-positive and Gram-negative bacteria [136][137][138][139][140][141].…”
Section: Php?ids[]=saandids[]=egandids[]=ptandids[]=b Randids[]=it (A...mentioning
confidence: 99%
“…Total phenolic acid and flavonoid content, hydrogen peroxide removal activity, the effect of removal of DPPH radicals, total antioxidant capacity, and measurement of reduction potential are representative methods applied in honey research, to emphasize its nutritional and health-beneficial activities. Concerning the physicochemical properties of honey, specific emphasis was given to color, water and moisture content, organic acids, acidity and pH, electrical conductivity, and ash content [99,105,[140][141][142].…”
Section: Php?ids[]=saandids[]=egandids[]=ptandids[]=b Randids[]=it (A...mentioning
confidence: 99%
“…They reported that the total phenolic contents were 14.52, 26.88 and 32.67 mL/g for the stages of vegetative, flowering and seed ripening, respectively. Various parts (roots, flowers, shoots) of the heather plant contain important bioactive compounds and chemical composition of the heather plant is depended on some factors such as the climate, season, altitude, soil characteristics or growth stages (Cucu et al, 2022).…”
Section: Total Phenolic Content Of the Tincture Samplesmentioning
confidence: 99%
“…The separation of natural bioactive chemicals from plants can be accomplished utilizing cutting-edge, high-tech, hyphenated chromatographic approaches, which also provide us with lots of information to be able to identify compounds [5][6][7]. In order to explain a plant's mechanism of action and therapeutic effect, modern healthcare providers need to be able to link the phytochemical profile of a plant employed in therapy to a biological activity [8]. In addition to plants, natural bioactive substances can be found in a variety of foods and pharmaceuticals [8,9].…”
Section: Introductionmentioning
confidence: 99%